2017
DOI: 10.1186/s40199-017-0181-1
|View full text |Cite
|
Sign up to set email alerts
|

Forensic toxicology analysis of self-poisoning suicidal deaths in Tehran, Iran; trends between 2011-2015

Abstract: BackgroundSuicide ranks among the top ten causes of death in all age groups all over the world. There are many methods for committing suicide including self-poisoning, firearm and hanging. The aim of the present study was to provide an overview of self-poisoning related suicidal deaths with special focus on forensic toxicology analysis results in Tehran, Iran from 2011 to 2015.MethodsAll suspicious cases with the the history of self-poisoning were investigated to define the cause and manner of death under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 61 publications
(81 reference statements)
5
34
0
2
Order By: Relevance
“…The cause of death of 10 cases in the present study was suicidal death with toxic agents. Our findings provide more evidence for the other studies, in that there is a strong association between drug abuse and suicidal ideation .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The cause of death of 10 cases in the present study was suicidal death with toxic agents. Our findings provide more evidence for the other studies, in that there is a strong association between drug abuse and suicidal ideation .…”
Section: Discussionsupporting
confidence: 82%
“…It may be suggested that the cause of death of many cases in the current study was the cardiotoxic effect of methadone ameliorated by concomitant use of methamphetamine. Non‐medical use of pharmaceutical drugs is a significant problem in many countries and Iran . Replacement of illicit drugs with psychoactive prescription drugs (methadone, tramadol and buprenorphine) has led to greater demand for addiction treatment and also death .…”
Section: Discussionmentioning
confidence: 99%
“…For toxicological analysis, urine samples were extracted by liquid-liquid extraction (LLE) in systematic toxicological analysis (STA) manner for screening drugs, poisons, and opioids (Kordrostami et al 2017). As novel psychoactive substances are not available and routinely used in Iran, we did not search for them in biological specimens.…”
Section: Methodsmentioning
confidence: 99%
“…As many drugs of forensic interest have alkaline chemical structure, the pH of the urine sample was adjusted to basic (pH = 12) for efficient extraction of alkaline drugs such as narcotic analgesics, benzodiazepines, and ATS. Careful adjustment of pH to 8.5-9 was needed for the extraction of amphoteric drugs such as morphine using LLE method (Kordrostami et al 2017). For the extraction of acidic drugs such as phenytoin, barbiturates, and pyrimidine, the pH of experiment medium was adjusted to 2.…”
Section: Methodsmentioning
confidence: 99%
“…However, our examination of patients with severe intoxication indicated that sex was unrelated to survival. The incidence of severe intoxication among different age groups also varied in previous studies (17,23,27). We found that elderly patients were more likely to die from severe intoxication.…”
Section: Discussionmentioning
confidence: 50%